Women, Water and Memory: Recasting Lives in Palestine by Nefissa Naguib (Leiden, The Netherlands: Brill, 2009. pbk. 176 pages) (American Journal of Islam and Society, 2011)
Nefissa Naguib’s book is the third in Brill’s Women and Gender series. It isan interdisciplinary study comprising an anthropological discussion, socialgender theories, and a geographical discussion. The book is primarily basedon anthropological research and presents the stories of eight women fromthe Palestinian village of Musharafah—and by means of which, it createsa discourse that examines the changes that have taken place in the status ofwomen in Palestinian society, and their functioning following the politicaland economic changes in Palestinian society in general, and in Musharafahin particular. Water is the connecting thread between the stories of the eightwomen and the analysis of their social functioning in the village.The extensive preface to the book is part of a long theoretical introduction,in which the author explains that “It is a story about how water is anendlessly evolving enactment of gender, family and community relationships”(1). She reviews the aims of the book in general, provides a generaldescription of the village and its women, and discusses terms—such as“society of women”—which she will use extensively in the book. The secondpart of the theoretical introduction, entitled “The Women and TheirStories,” describes the way of life that is a backdrop for the women’s stories,and the importance of water as a component in each story.The book is comprised of two parts. Part 1, “About Musharafah,” includesthe first two chapters, which also constitute a theoretical review,and serve as the basis for the anthropological study and analysis in Part 2 ...